(untitled) (Heritage, 2023)
In the process of European integration, cultural integration as a social process is gaining more and more importance. The subject of this paper refers to the role of culture in the European integration of Serbia. The paper will examine the approach that is focused on cultural integration towards the process of European integration, precisely because of the inevitability of the need to consider culture within the framework of international integration. The cultural diversity of European Union member countries and candidates for membership points to the fact that the most important problem of European integration is to find out how to deal with cultural differences. It is precisely these differences that make the European Union a unique organization in the world. It is precisely the respect for cultural diversity that makes the European Union open to new members - current candidates for membership. The aim of this paper is to point out the great importance and role of culture in European integration.